Plan de negocios, mediante la aplicación de la metodología de Canvas, para proponer la creación de un centro de eventos y banquetes "D՝ Lago", en la parroquia Nueva Loja - Calderón Ramírez, José Gabriel (2016)
The research work was done in the parish Nueva Loja, in order to determine the feasibility and propose the creation of an establishment called Events and Banquet Center "D` Lago", causing discomfort in the organization of local people and enjoy all kinds of social and cultural event due to scarce local that have comfortable, adequate, safe, that meets your needs and provide good service infrastructure. Given the purpose of the above, three specific objectives: Conduct a situational analysis of the area; Apply CANVAS methodology; Set design center infrastructure E & B. To fulfill the objectives fieldwork was carried out using techniques directly to establishments of food, beverages and hotel observation; the implementation of the survey of 102 people including locals, national and international tourists, the information analysis of statistical data INEC was held 9 modules CANVAS methodology was applied using deductive and analytical methods; and infrastructure design method was performed using architectural design. The following results: it was determined that there are 35 places that serve food and beverage, 6 hotels that have small spaces established for family gatherings. It was verified that the potential group (client) are residents of the sector, which have 2 to 4 family members, have average income of $500,00, mostly celebrate birthdays baptisms and marriages, averaging 2 events per year and show you would like: Innovation company, good infrastructure, complete and economical service. Economically Active Population is 37,961; trading activity 87%, services 8.10% and 4.9% in manufacturing activities, crafts, agriculture and construction. Construction was established in 3.550m2 area, with implantation of a plant 1.242m2 concrete and metal structure covered with 169,233.27 dollars investment.